Recurrent vaginal discharge: an unusual presentation of embryonal rhabdomyosarcoma of uterine cervix in an adolescent girl - Sarin, Divya; Singh, Urmila; Mehrotra, Seema; Solanki, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Embryonal rhabdomyosarcoma (ERMS) is a rare tumor of the female genital tract. It tends to occur during childhood in the vagina and rarely it can arise in the uterine cervix, with a peak incidence in the second decade. We report a case of 15 year old adolescent girl who presented with recurrent vaginal discharge not responding to medical treatment. Examination under anesthesia showed friable growth arising from the cervix. Histopathological examination revealed embryonal rhabdomyosarcoma (botyroid variant) of the cervix. Patient underwent local excision of growth followed by IRS-4 protocol based chemotherapy and now patient is under follow up at our side and pediatric oncology and doing well. Young girls presenting with recurrent vaginal discharge not responding to medical treatment must undergo proper clinical examination and EUA and any suspicious lesions should be examined so as to avoid missing rare but aggressive etiology like rhabdomyosarcoma. Due to the young age of affected patients, embryonal rhabdomyosarcoma (sarcoma botyroides) poses a management challenge as the preservation of hormonal, sexual and reproductive function is essential. Awareness of such as uncommon lesion and its clinical implications is important for the counseling and management of the patient.